Perancangan Sistem Informasi Pendataan Inventory Aset pada Depot Kayu Kusen Laris III - Muhammad Tengku Sadewa; Tata Sutabri (Switch : Jurnal Sains dan Teknologi Informasi, 2025)
During this time, the development of technology has progressed rapidly. In this sense, many companies have followed this technological development and introduced it into the collection of inventory data of assets, goods, and their financial reports. To obtain accurate and precise data, an inventory data collection system is required. Manual accounting calculations mean that Depot Kayu Kusen Laris III often records inventory incorrectly, which affects the resulting financial reports. Therefore, this study aims to develop an inventory information system that will support accurate data collection at Kayu Kusen Laris III Depot. The conclusion of this study is that the inventory data information system is designed using Access and SQL database.